Heckscher, Mercantilism - Haley, B. F. (Quarterly Journal of Economics, 1936)
Journal Article Heckscher, Mercantilism Get access B. F. Haley B. F. Haley Stanford University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 50, Issue 2, February 1936, Pages 347–354, https://doi.org/10.2307/1885028 Published: 01 February 1936